Domestic, Foreign or Common Shocks? - Fabrizio, Stefania (IMF Working Papers; Working Paper, 1996)
A stochastic general equilibrium model of the world economy is used to analyze the origin of international business cycles using data for Germany, Japan and the United States. The findings indicate that after 1973, common shocks play a major role in accounting for similarities in output fluctuations. However, trade interdependencies with the United States may have also played a very important role; more than 20 percent of output fluctuations of the German and Japanese economies could have been imported from the United States.